Covid-19 Effect on Herding Behaviour in European Capital Markets - Espinosa-Mendez, C (Elsevier Ltd, 2021)
This article investigates whether COVID-19 pandemic had an effect on herding behaviour in Europe. Using a sample from the stock exchanges of France (Paris), Germany (Frankfurt), Italy (Milan), United Kingdom (London) and Spain (Madrid), over the period from January 03, 2000 to June 19, 2020, we found robust evidence that COVID-19 pandemic increased herding behaviour in the capital markets of Europe. © 2020 Elsevier Inc.